v.1 - Gupta, U. N. (New Delhi, 2009)
Each of the 192 states in the world has its systems of laws enshrined in its Constitution. Each Constitution has certain identifiable characteristics depending upon the system of government preferred by its framers, like democracy, monarchy, republic, autocracy, federal or religious state, etc. There are different systems and procedures within each of these categories on the basis of which each state can be identified and studied. The general features of the Constitution include, inter alia, the relative importance of legislative, executive and judicial branches of government along with the purposes or ideals sought to be achieved by the state such as freedom of the individual, equality, maintenance of public order and promotion of civil liberties. However, in many new states formed after the breaking up of large empires, the political theories have been put on the back-burner, and new set-ups that facilitate rapid economic growth are now being preferred. Many new as well as old states are now giving precedence to a combination of different constitutional theories to suit their socio-political, religious and economic heritage. Select World Constitutions, in two Volumes, encompasses the main provisions and articles of 13 landmark Constitutions of the world. Volume I covers the Constitutions of United Kingdom, United States of America, Australia, Federal Republic of Germany, Canada, South Africa, and Japan. Volume II includes the Constitutions of France, Swiss Confederation (Switzerland), People$1 (Bs Republic of China, Sri Lanka, Kingdom of Bhutan, and Singapore. The Constitutions of Pakistan and Nepal$1 (Btwo important countries of the Indian subcontinent$1 (Bhave not been included because they continue to be in a fluid state with persistent political uncertainties. The book will prove immensely useful to the students and teachers of political science and researchers in this field. It is an ideal reference source for legislators, lawyers and those concerned with the working of a political system. Common readers will also find it inculcating and informative.s
Keywords: Constitutions-World